2022
DOI: 10.1371/journal.pone.0272664
|View full text |Cite
|
Sign up to set email alerts
|

CALMS: Modelling the long-term health and economic impact of Covid-19 using agent-based simulation

Abstract: We present our agent-based CoronAvirus Lifelong Modelling and Simulation (CALMS) model that aspires to predict the lifelong impacts of Covid-19 on the health and economy of a population. CALMS considers individual characteristics as well as comorbidities in calculating the risk of infection and severe disease. We conduct two sets of experiments aiming at demonstrating the validity and capabilities of CALMS. We run simulations retrospectively and validate the model outputs against hospitalisations, ICU admissio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
2
1

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 47 publications
0
3
0
Order By: Relevance
“…Following full text screening of 358 studies, 40 articles were included, having met our eligibility criteria. 2160 A further six eligible studies were identified through screening reference lists of included studies, 6166 and one additional study was discovered through searching for papers describing the European COVID-19 Scenario Hub models, 67 giving a total of 47 studies included in our review. Out of the 47 included studies, there were 40 unique models; five models were used in more than one paper.…”
Section: Resultsmentioning
confidence: 99%
“…Following full text screening of 358 studies, 40 articles were included, having met our eligibility criteria. 2160 A further six eligible studies were identified through screening reference lists of included studies, 6166 and one additional study was discovered through searching for papers describing the European COVID-19 Scenario Hub models, 67 giving a total of 47 studies included in our review. Out of the 47 included studies, there were 40 unique models; five models were used in more than one paper.…”
Section: Resultsmentioning
confidence: 99%
“…Examples of these include the propagation of knowledge across communities and the spread of infectious diseases on a local, individualized level. To specifically address the latter challenge, we instead developed a different simulation kernel (the Flu And Coronavirus Simulator [33], [35]) which is better suited to efficiently calculate the outcomes of large numbers of interpersonal interactions.…”
Section: Reuse Potentialmentioning
confidence: 99%
“…Three simulation models were used in the workshop that model different aspects of the COVID-19 pandemic. These include the dynamiC Hospital wArd Management (CHARM) Discrete-Event Simulation (DES) for hospital bed capacity management (Anagnostou et al, 2022), the Flu and Coronavirus Simulation (FACS) Agent-Based Simulation (ABS) that models the geospatial spread of the disease and the impact of preventive measures (Anagnostou et al, 2022), and the CoronAvirus Lifelong Modelling and Simulation (CALMS) ABS that considers long-term policy intervention effectiveness (Mintram et al, 2022).…”
Section: The Project and The Need To Consider These Issuesmentioning
confidence: 99%